Janitor’s Attitudes: Their Effect on Performance at La Consolacion University Phippines SY 2020-2021 - Estacio, Dennis L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The purpose of this research project was to evaluate attitudes of the janitorial workforce in La Consolacion University Philippines of S.Y. 2020-2021 in order to ascertain whether there is a direct relation to their performance. An attitude is a psychological state of mind. It is the way a person thinks about situations, and it ultimately determines a person's behavior. In the workplace, employees can have either a positive or negative attitude about specific work tasks, products or services, co-workers or management, or the company as a whole. Positive attitudes among employees make workdays more enjoyable. Tasks are performed to a higher standard and without complaint. An example of a positive employee attitude occurs when an employee views a negative customer service call as an opportunity to change the narrative for the customer from a bad experience to a good one. However, bad attitudes result in apathy to daily tasks. Employees are easily agitated by minor problems. Tasks are completed at substandard levels (Leonard, 2018). Job attitudes such as satisfaction and involvement are criterion for establishing the health of an organization; rendering effective services largely depends on the human resource. Job satisfaction experienced by employees will induce the people to give their best to the organization. Both the attitudes required to enhance the performance of employees. Current study is based on the effect of attitude on employee performance. This study include the attitude related factors (behaviors of employees and leaders, job satisfaction, job commitment, motivation and training) to investigate their impact on employee performance. This study utilized descriptive method of research. An instrument was developed by the researcher with 8 statements to measure the perceived level of satisfaction, involvement, and performance and then distributed among the respondents with the five- point Likert scale In the totality, respondents rated majority of the janitors with an approval rating of VERY GOOD to the four janitors and GOOD to the Five Janitors while three of the Janitors got an average rating of FAIR. Result shows that all attitude related factors positively affect the employee performance. Motivation and job commitment has highly significant impact of performance of employees. As a result, organizations should value their experienced personnel and devise effective retention policy by giving competitive salary, experienced base pay and experienced based promotion. That will increase the overall performance of the organization. Janitors have to change their poor attitudes and must exhibit more dedication towards their job. Other employees have to make effort to correct these attitudes that is affecting the work. The following are recommendations to improve values and attitudes and to increase the individual performance: Let the janitors feel the sense of total belongingness and importance not to let them feel that they are categories into the lower level of the organizations, let them be involved and participate in all institutional activities to establish camaraderie. Identifying the negative of bad attitudes of the janitors and provide corresponding trainings and seminars to correct their attitudes resulting to poor performance at work. Motivating employees to achieve the high level of satisfaction and performance by giving appropriate awards and incentives. Ensure feedback is specific – Don't just tell the employee their poor attitude needs to improve. Point out exactly what negative traits they have and the impact each has on their performance and monitor their action periodically for expected change to positive attitude towards work performance. Generally, workers with good attitudes have stronger performance, and workers with poor attitudes exhibit less-than-superior performance. It is up to managers to monitor employee attitudes and address attitude problems such as negativity and laziness.